IMPLEMENTASI TEORI PERTUKARAN PADA LEMBAGA KEUANGAN SYARIAH DI INDONESIA - Lubis, Rusdi Hamka; Fuad, Ahmad (Syari'ah, 2019)
This study aims to explain the transformation of exchange value in meeting the needs of human life on this earth. Exposure to theories and practices of exchange in increasingly modern economic values forces people to compete with each other. The emergence of an economic system in the form of a market to facilitate humans. Bank and financial industry are one of the modern instruments. Conclusion of the research with the literature study method, that Sharia Banking or Sharia Financial Institutions are not only the banking sector based financial systems as Conventional Banking but Sharia Banking is sector-based banking real, transactions in the real sector of Islamic banking involve 'ayn (goods) and dayn ( financing), so that exchange theory is an important thing implemented in meeting basic human needs.